Revisiting the molecular epidemiology of factor XI deficiency: Nine new mutations and an original large 4qTer deletion in western Brittany (France) - Guéguen, Paul; Chauvin, Angélique; Quémener-Redon, Sylvia; Pan-Petesch, Brigitte; Férec, Claude; Abgrall, Jean-François; Maréchal, Cédric Le (Thrombosis and Haemostasis, 2012)
Constitutional deficiency in factor XI (FXI) is a rare bleeding disorder in the general population, with the exception of Ashkenazi Jews. During the last decade, the detection of FXI-deficient patients has shifted from clinical screening identifying mostly severe bleeders to biological screening combining findings of prolonged activated partial thromboplastin time and FXI coagulation activity (FXI:C) below 50 U/dl. The goal of this study was to determine the molecular basis of FXI deficiency in western Brittany, France. Over the course of four years, we detected 98 FXI-deficient patients through biological screening, and 44 patients agreed to participate in this study corresponding to 25 index cases. We developed an efficient mutation detection strategy (combining direct sequencing and QFM-PCR to search for heterozygous rearrangements in a routine setting) that detected F11 mutations in 24 out of the 25 index cases. An unexpected allelic heterogeneity was found, with 14 different single point mutations being detected, among which nine are new. Moreover, a large heterozygous deletion of the entire F11 gene was detected, and was then further defined using a CGH array as a 4q34.2 telomeric deletion of 7 Mb containing 77 genes. We propose that the observed recurrent mutations may be considered as genetic tags of a population. This study highlights the importance of screening for large deletions in molecular studies of F11.
Keywords: Factor XI deficiency; genetic analysis; mutation; deletion; F11 gene